ANALYSIS OF SOCIAL MEDIA MARKETING AND INFLUENCER ENDORSEMENT ON CONSUMER LOYALTY THROUGH CUSTOMER SATISFACTION IN PURCHASING MUSLIM FASHION PRODUCTS IN E-COMMERCE - Natari, Dian; Endang Sulistya Rini; Sembiring , Beby Karina Fawzeea (DAS CONFERENCE INTERNATIONAL SERIES, 2025)
The purpose of this study is to determine directly and indirectly the relationship between social media marketing and influencer endorsement on customer loyalty through customer satisfaction. The population in this study are all Muslim fashion consumers who shop in e-commerce such as Shopee, Tokopedia, Lazada, and Blibli, the number of which could not be known with certainty. The sample withdrawal used is accidental sampling, distributing questionnaires using google forms. The research sample was taken using the Zikmund formula so that a sample size of 150 respondents was obtained. Data analysis was carried out using structural equation modeling (SEM) techniques with Smart-PLS analysis tools to test the direct and indirect relationships between these variables. The results explain that social media marketing directly has a significant effect on customer satisfaction, influencer endorsement directly has a significant effect on customer satisfaction, social media marketing directly has a significant effect on customer loyalty, influencer endorsement directly has a significant effect on customer loyalty, customer satisfaction directly has a significant effect on customer loyalty, social media marketing indirectly has a significant effect on customer loyalty through customer satisfaction and then influencer endorsement indirectly has a significant effect on customer loyalty through customer satisfaction.